Hubungan Dukungan Keluarga terhadap Kualitas Hidup Pasien Diabetes Melitus Tipe 2 - Mulia, Madepan; Fitarina, Fitarina (AKPER Dharma Wacana, 2025)
Diabetes mellitus with complications can significantly impact a patient's quality of life, making family support essential in managing the condition. Family support plays a vital role in the treatment and care process for individuals with type 2 diabetes mellitus. The purpose of this study was to explore the relationship between family support and the quality of life of type 2 diabetes mellitus patients. The research employed a quantitative approach with a cross-sectional design. It was conducted on 100 type 2 diabetes mellitus patients at the Pesawaran Regional General Hospital, using incidental sampling and questionnaires. The family support was assessed using the HDFSS, while the quality of life was measured with the DQOL questionnaire. Data analysis was performed using the Chi-Square test, with a significance level of 0.05 and a confidence interval of 95%. The findings revealed that 63% of type 2 diabetes mellitus patients received high family support, but 62% of them reported a low quality of life. A significant relationship was found between family support and the quality of life of type 2 diabetes mellitus patients (p=0.016). In conclusion, family support is linked to the quality of life in type 2 diabetes mellitus patients. It is recommended that families increase their support, and nurses should encourage families to provide more support to improve the patients' quality of life.